2008
DOI: 10.1007/s10695-008-9227-0
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting actions of bisphenol A and malachite green on growth hormone receptor gene expression and signal transduction in seabream

Abstract: Environmental estrogen could mimic natural estrogens thereby disrupting the endocrine systems of human and animals. The actions of such endocrine disruptors have been studied mainly on reproduction and development. However, estrogen could also affect the somatotropic axis via multiple targets such as growth hormone (GH). In the present study, two endocrine disruptors were chosen to investigate their effects on the expression level and signal transduction of growth hormone receptor (GHR) in fish. Using real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…EE such βS and NP have been found to bind to the estrogen receptor in mammals and teleosts, albeit with a much lower affinity than E2 (Bonefeld-Jorgensen et al, 2001;Tremblay and Van der Kraak, 1998;Knudsen and Pottinger, 1999;Sumpter and Jobling, 1995), which may explain the observed differences in potency and efficacy. ERα mediated E2 and bisphenol A (BPA) attenuated GH signaling as reflected by reduced GH-induced expression of casein in Hepa-T1 cells cotransfected with seabream GHRs (Jiao and Cheng, 2010). ER dependence of EE action appears conserved from fish to mammals as E2-, NP-, BPA-altered GH expression in rat pituitary GH3 cells also could be blocked by ER an antagonist (Dang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…EE such βS and NP have been found to bind to the estrogen receptor in mammals and teleosts, albeit with a much lower affinity than E2 (Bonefeld-Jorgensen et al, 2001;Tremblay and Van der Kraak, 1998;Knudsen and Pottinger, 1999;Sumpter and Jobling, 1995), which may explain the observed differences in potency and efficacy. ERα mediated E2 and bisphenol A (BPA) attenuated GH signaling as reflected by reduced GH-induced expression of casein in Hepa-T1 cells cotransfected with seabream GHRs (Jiao and Cheng, 2010). ER dependence of EE action appears conserved from fish to mammals as E2-, NP-, BPA-altered GH expression in rat pituitary GH3 cells also could be blocked by ER an antagonist (Dang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…1A). 73,225 These studies showed effects on liver enzymes and markers of oxidative stress, potential markers of liver function, at or below 10 -9 M; two other in vitro studies found effects of higher doses on similar endpoints. 226,227 In laboratory animals, four studies showed low dose effects on the expression of liver enzymes and hepatic gene expression (Fig.…”
Section: Integration Of Endpoints Across Levels Of Biological Organizmentioning
confidence: 97%
“…While it was shown to bind to a range of hormone receptors (human: Prasanth et al 2010; fish: Jiao and Cheng 2010), there has been particular interest in BPA binding to estrogen receptors (ER), e.g., ERα, ERβ, and estrogen-related receptor gamma, ERRγ (general vertebrate: Ben-Jonathan and Steinmetz 1998; human: Takayanagi et al 2006; fish: Saili et al 2012; mice: Kundakovic et al 2013; rat: Cao et al 2013;). To explain differences in behavioral responses to BPA exposure by males vs. females, Masuo and Ishido (2011) and Kubo et al (2001) suggest BPA action in the locus ceruleus, especially in males.…”
Section: Introductionmentioning
confidence: 99%